Solubility behaviour of CL-20 and HMX in organic solvents and solvates of CL-20 - Dirk Herrmannsdörfer; Jörg Stierstorfer; Thomas M. Klapötke (Energetic Materials Frontiers, 2021)
2,4,6,8,10,12-Hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (CL-20) and 1,3,5,7-tetranitro-1,3,5,7-tetrazoctane (HMX) are promising cocrystal coformers, but only little solubility data are available. Knowledge about their solubility and solvate formation is essential for the development of cocrystallisation experiments. This paper provides the solubility values of HMX and CL-20 in 29 solvents at 293.15 ​K and 333.15 ​K as well as the solubility in five 2-propanol solvent mixtures at 293.15 ​K. Novel CL-20 solvates of 5-methyloxolan-2-one, 1,3-dioxolan-2-one, tetrahydrotiophene 1-oxide, 1,3-dioxolane, furan-2-carbaldehyde and butane-2,3-dione have been isolated and characterised. For all new solvates, single crystal data were obtained, except for furan-2-carbaldehyde. The novel ϑ-conformation of CL-20 was observed in the tetrahydrotiophene 1-oxide solvate. It was found that none of the tested solvents and likely no existing solvent exhibits a beneficial solubility ratio of CL-20 and HMX in the tested temperature range, exceptionally good solubility ratios are most likely the result of solvate formation, and that solvate forming solvents cannot be categorically excluded from consideration as solvent for cocrystallisation of HMX and CL-20.